Cardiovascular Disease Protective Effect of Allicin Through Gut Microbiota Modulation (FS07-08-19) - Chen, Chen Pei (Curr Dev Nutr, 2019)
OBJECTIVES: Red meat consumption can promote atherosclerosis since the gut microbiota can metabolize L-carnitine from meat into trimethylamine N-oxide (TMAO) which is a causative risk for cardiovascular disease. Garlic has long been associated with health benefits. Allicin is a major bioactive compound typically found in blend fresh garlic. It possesses the antibacterial, anti-oxidant, and cholesterol-lowering effects. The aim of this study is to investigate the effect allicin on the gut microbiota and its metabolites on cardiovascular disease by using the long-term carnitine treatment ApoE (-/-) mice model. METHODS: 8-week old male ApoE (-/-) mice were divided into 4 groups: (1) Control, (2) 1.3% Carnitine, (3) Allicin (10 mg/kg), and (4) 1.3% Carnitine + Allicin (10 mg/kg). After 15 weeks, we performed the carnitine challenge test by oral gavage of d9-carnitine to evaluate the TMAO production ability of the gut microbiota. The serum was analyzed for carnitine, trimethylamine (TMA) and TMAO levels by using LC-MS/MS. Other biochemistry was checked by an automatic blood analyzer. Morphological changes of aortic plaque formation were observed using oil red staining. The gut microbiome was analyzed by using 16S rDNA amplicon sequencing in Illumina Miseq platform. RESULTS: The results showed that allicin supplementation in the carnitine group exhibited the reduction of aortic lesion up to 34.2% as compared with carnitine group without allicin supplementation (P < 0.01). The carnitine challenge test indicated the d9-TMAO level of carnitine with allicin supplementation group tend to be reduced compared with carnitine-fed mice. Principal coordinate analysis of the feces microbiota composition was significantly different (ADONIS: P < 0.001) for each group. The linear discriminant analysis (LDA) effect size (LEfSe) results demonstrated that Akkermansia was enriched in the carnitine-fed group. In contrast, the carnitine-fed mice with allicin supplementation were abundance with Lachnospiraceae. CONCLUSIONS: Allicin may exhibit the cardiovascular disease protective effect through modulation of gut microbiota-TMAO-atherosclerosis pathway. FUNDING SOURCES: MOST 107-2321-B-002 -017 -. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: